Exploring structures and beliefs underlying textbook praxis in German foreign language courses at a South African university "“ a social realist perspective - Engelbrecht, Natasha (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Commercial textbooks, aligned with the Common European Framework of Reference for Languages (CEFR), are prescribed in almost all undergraduate GFL courses offered at South African universities. Although providing practical relevance and quality assurance, the CEFR-level descriptors were developed for the European context. The projected relevance and appropriateness of teaching materials presently implemented in German curricula in South African higher education have been determined in Germany, not for local contexts, but for learners vaguely described as "Anfänger" (Evans, et al., 2012, p. 8) and "Erwachsene und Jugendliche ab 16 Jahren" (Hueber, 2019, p. 11), often with a focus on learning for prospective German immigrants or for the use in refugee- or immigrant integration courses. However, the textbook occupies a central position in the GFL course because of the structured grammar progression that it lends to the curriculum. The variety of resources available to lecturers (tests, worksheets, online learning platform) and students (exercises, English-German glossary, English grammar explanations) is also an asset to GFL courses. Calls for the transformation and decolonisation of higher education have prompted academic disciplines to re-evaluate the common-sense assumptions which underpin knowledge practices in their curriculum. Following a social realist perspective and an exploratory case-study approach, this study presents a critical analysis of the textbook prescribed in the German Studies 1 course at Rhodes University and student experiences of the textbook to disentangle the complex relations which cause textbook praxis and lay bare power structures and tensions in the system.
Keywords: German language-- Study and teaching (Higher) English speakers; Curriculum change -- South Africa; German language Textbooks History and criticism; Common European Framework of Reference for Languages (Project); Decolonization -- South Africa; Educational change -- South Africa; Social realism